Implementation Of Supportive Psychotherapy In The Elderly In Jekan Raya District, Palangka Raya City - Syam'ani, Syam'ani; Kasuma , Wijaya A. (Utami Publisher, 2025)
The elderly population is a heterogeneous population: Not all individuals in the elderly population require the same form of social services. This is because the elderly population, although overall included in the fragile health/welfare population group, but to varying degrees. This difference is seen not only from the health aspect (some are